5PSQ-008 Assessment of patient-controlled analgesia (PCA) practices in a public hospital. (23rd March 2022) - Trocherie, L; Rogé, M; Pozzi, D; Pons-Kerjean, N
Abstract : Background and importance: PCA pumps help patients manage their pain by guaranteeing them autonomy, while lightening nursing workload. In this context, the prescriptions must contain the information necessary for secure programming (background dose, bolus, inter-dose, etc .) leaving no possibility for interpretation. This project was founded in response to repeated adverse event reports concerning patient-controlled analgesia ( PCA) (8 reports between 2017 and 2020 with a majority of overdoses requiring care). Aim and objectives: An assessment of the prescription and monitoring of PCA is carried out with the aim of having a database in order to standardise the method of prescription using a multidisciplinary working group. Material and methods: Information is collected through an interview of the health executive of each department using a seven-item questionnaire: prescription, monitoring, pump use, clarity of prescription, nurse skills and presence of a pain-referent (specialised nurse). The information was collected in the care unit using PCA between June and September 2021. Results: Seven department health executives were interviewed. Concerning the prescription: five departments use a computerised prescription, none include dilution information, and programming details are added by the prescriber because there is no prepared protocol. Two services use a paper prescription that is also the follow-up paper: they contain dilution information but not the background dose. Five services carry out the follow-up with a paper follow-up sheet, which differs according to the service, and two services use written computer transmissions. Concerning the other items: there is a lack of training sessions about the PCA pump use, only one service had a recent course by the company. Conclusion and relevance: The assessment showed a disparity in the method of prescription and monitoring. It appears that essential data are missing, data which are necessary to have a complete prescription. It would be interesting to work on a computer protocol making it possible to simplify the prescription (basic dose, bolus, inter-dose, etc.), as well as to propose a single paper prescription for non-computerised services. A working group comprising representatives of the pharmacy department, prescribers from the care units concerned, health executives and pain-adviser nurses has been set up to work on this issue with the objective of improving patient care. References and/or acknowledgements: Conflict of interest: No conflict of interest